THE STRATEGY OF AN ISLAMIC BOARDING SCHOOL OF PANGERAN DIPONEGORO IN YOGYAKARTA TO PRESERVE ITS EXISTENCE THROUGH CHARACTER EDUCATION BUILDING TOWARD STUDENTS - Muna, Choirul; Sodik, Fajar (Edusoshum : Journal of Islamic Education and Social Humanities, 2021)
Nowadays, the issue of character education is spreading, given the various events that have occurred, so that the determination of the youth of this country has fallen so sharply. This study aims to analyze the strategy of the Prince Diponegoro Islamic Boarding School in Yogyakarta in maintaining its existence through the cultivation of character education for students. This type of research is a type of qualitative research. The results of this study are the Prince Diponegoro Islamic Boarding School, Yogyakarta, managed to maintain its existence in the midst of the presence of modern education. The Islamic boarding school through its educational programs with existing methods is able to continue to exist. The strategies implemented such as the exemplary method, the habituation method, the mau`izhah method or advice as well as the motivation and intimidation method were considered optimal and able to change the character of the santri for the better. so that many guardians of students believe and leave their children in the boarding school.